Perancangan taman edukasi di Sekolah Harapan Bunda Jimbaran - Afaraby, Ferry Zulkifli Febrian; Yusiana, Lury Sevita; Utami, Ni Wayan Febriana (Jurnal Arsitektur Lansekap; Vol.7, No.1, April 2021, 2021)
School is a place for students to learn and build their character. Meanwhile, environmental damage caused by human activities is increasing, so that environmental awareness on school need to be developed by providing educative facilities in the form of school open space. This created to fullfill comfortable school environments while providing educative facilities and build environmental awareness of students with the adiwiyata concept which is a school program aims to encourage schools to adopt behaviors that are respectful towards the environment. This research was conducted at Harapan Bunda School (HBS), Jimbaran, Bali which has a large open space area but has not been optimized. Several facilities have been damaged due to dysfunction. The study aims to design a gardenbased learning area to optimize the potential of the outdoor space and solve the problem in the HBS. Method used in this research was field survey by implementing data collection techniques such as observation, interviews, questionnaire and literature studies. The results showed that the SHB area was designed by dividing the area into three main area i.e. activity areas, functional areas and areas of space requirements. Areas of activity include active and passive areas. Whereas, functional areas include reception areas, connecting areas and main areas. According to space requirements, the area were divided into built areas, open space and green open space equipped with pergola facilities and some benchs to support passive activities and playing fields to support active activities. Hydroponic areas and vertical gardens are also provided support green open spaces.